2014
DOI: 10.1177/1098612x14560101
|View full text |Cite
|
Sign up to set email alerts
|

Globe penetration in a cat following maxillary nerve block for dental surgery

Abstract: Complications arising from veterinary dental regional anaesthesia appear to be rare; however, it may be that they are under-reported. This case report highlights the risks involved and reviews the safest and most efficacious regional anaesthesia technique for the feline maxilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
0
19
2
Order By: Relevance
“…This finding may have resulted from inadequate technique and deposition of methylene blue dye in close proximity to the eye globe or migration of dye from the place of injection. Other macroscopically observed events reported in previous studies, such as intraneural or intravascular injection and damage to the peribulbar tissue, were not evidenced in the present study (GROSS et al, 2000;PERRY et al, 2015). However, such complications might be difficult to observe in a cadaver study if histopathology or MRI was not performed.…”
Section: Veterinarian Sbz Iocontrasting
confidence: 58%
See 1 more Smart Citation
“…This finding may have resulted from inadequate technique and deposition of methylene blue dye in close proximity to the eye globe or migration of dye from the place of injection. Other macroscopically observed events reported in previous studies, such as intraneural or intravascular injection and damage to the peribulbar tissue, were not evidenced in the present study (GROSS et al, 2000;PERRY et al, 2015). However, such complications might be difficult to observe in a cadaver study if histopathology or MRI was not performed.…”
Section: Veterinarian Sbz Iocontrasting
confidence: 58%
“…There are several local anesthetic techniques described in dogs and cats with the aim of providing analgesia for specific regions of the head, including the oral cavity (FUTEMA et al, 2002;BARDELL et al, 2010;VISCASILLAS et al, 2013). Maxillary nerve is a branch of the trigeminal, which provides sensory information to the skin of the upper lips and nostrils, as well as the soft and hard palate, upper teeth, gingiva and maxilla (DELLMANN & MCCLURE, 2008;PERRY et al, 2015). Therefore, maxillary nerve blockade provides anesthesia for selected procedures such as rhinoscopy, maxillectomy and upper teeth extractions (CREMER et al, 2013).…”
Section: Clinic and Sugerymentioning
confidence: 99%
“…Furthermore, a cadaver study in dogs showed the infraorbital approach for the maxillary nerve block, using an intravenous catheter, to be more suitable and safer compared with the percutaneous approach 15. Also, ocular side effects have been reported after maxillary nerve block performed by the transcutaneous approach in dogs and cats 32 33. In the present report, the maxillary nerve block through the infraorbital canal seemed an easy and suitable regional anaesthesia technique for intraoperative pain management in lactating wallabies undergoing maxillary surgery, without any clinical side effects.…”
Section: Discussionmentioning
confidence: 54%
“…Inadvertent ocular penetration with needles used to administer local anesthetic has been documented or suspected in a number of cats and dogs. [9][10][11] All previously reported cases have been linked with dentistry-associated caudal maxillary blocks, in which the anesthetic delivery device is inserted percutaneously or intraorally at the junction of the maxilla and zygomatic arch, caudal to the last maxillary molar.…”
Section: Discussionmentioning
confidence: 99%